Varying circumstances surrounding opioid toxicity deaths across ethno-racial groups in Ontario, Canada: a population-based descriptive cross-sectional study - Tara Gomes; Mina Tadrous; Sophie A Kitchen; Frank Crichlow; Tonya J Campbell; Cynthia Damba; Colin H Johnson; Ashley Smoke (BMJ Public Health)
Introduction The North American toxic drug crisis has been framed as an epidemic primarily affecting white people. However, evidence suggests that deaths are rising among racialised people. Accordingly, we sought to describe and compare characteristics and circumstances of opioid toxicity deaths across ethno-racial groups.Methods We conducted a population-based, descriptive cross-sectional study of all individuals who died of accidental opioid toxicity in Ontario, Canada between 1 July 2017 and 30 June 2021. Decedents were categorised as Asian, black, Latin American or white. We summarised decedents’ sociodemographic characteristics, circumstances surrounding death and patterns of healthcare utilisation preceding death by ethno-racial group, and used standardised differences (SDs) to draw comparisons.Results Overall, 6687 Ontarians died of opioid toxicity, of whom 275 were Asian (4.1%), 238 were black (3.6%), 53 were Latin American (0.8%), 5222 were white (78.1%) and 899 (13.4%) had an unknown ethno-racial identity. Black people (median age: 35 years; SD: 0.40) and Asian people (median age: 37 years; SD: 0.30) generally died younger than white people (median age: 40 years), and there was greater male predominance in deaths among Asian people (86.2%; SD: 0.30), Latin American people (83.0%; SD: 0.21) and black people (80.3%; SD: 0.14) relative to white people (74.6%). Cocaine contributed to more deaths among black people (55.9%; SD: 0.37) and Asian people (45.1%; SD: 0.15) compared with white people (37.6%). Racialised people had a lower prevalence of opioid agonist treatment in the 5 years preceding death (black people: 27.9%, SD: 0.73; Asian people: 51.1%, SD: 0.22; white people: 61.9%).Conclusions There are marked differences in the risk factors, context and patterns of drug involvement in opioid toxicity deaths across ethno-racial groups, and substantial disparities exist in access to harm reduction and treatment services. Prevention and response strategies must be tailored and targeted to racialised people.